Schleiermacher's Hermeneutics and His Contribution to The Study of Hadith - Basayif, Muhammad Syamil; Amanullah, Mahasin Haikal; Amal, M. Khusna (AL QUDS : Jurnal Studi Alquran dan Hadis, 2024)
Contemporary hadith studies have involved many auxiliary sciences, one of which is hermeneutics. As a critical theory, hermeneutics has been utilized by hadith scholars to explore the meanings of hadith not only on the denotative but also on the connotative level. One of the hermeneutical theories that is worth considering and has not been widely used by scholars to read hadith texts is Schleiermacher's objective hermeneutics. Broadly speaking, the main ideas of objective hermeneutics emphasize grammatical interpretation, psychological interpretation, the hermeneutical circle, and the method of divination. Using library research, this study aims to examine the involvement of objective hermeneutics in the study of hadith which some scholars believe is not relevant enough. The results of the study show that the use of objective hermeneutics proves to be relevant and even contributes importantly to revealing the historical (asbabul wurud), epistemological (ulum al-hadis), and interpretive (syarh al-hadis) dimensions. Grammatical interpretation serves to explore á¸¥adÄ«Å› textually, psychological interpretation aims to read the context when the á¸¥adÄ«Å› appeared, the divination method serves to record the main ideas of the author, the hermeneutic circle is useful to dialogue between text and context until contextualization is born. Thus, Schleiermacher's hermeneutics makes an important contribution to hadith discourse in the modern era, without being uprooted from the roots of classical hadith discourse.